PORZĄDKUJĄCA FAZA WYKŁADNI PRAWA - Kanarek, Beata; Zieliński, Maciej (Wydział Prawa i Administracji UAM, 2001)
Within the framework of the derivative conception of interpretation of the law one can distinguish three groups o f problems: related to the problem of arranging (validating) regulations, related to the reconstruction of norm-like expressions from legal regulations, and finally, related to the perception of the norm content. The authors of the article focused on the first group, which, because of the various aspects of the role of the activities constituting this group, can be considered to be comprised of preliminary activities and can be called an arranging or validating phase. The term „phase” denoting a number of given activities, is supposed to emphasise their chronologically original character, irrespective of the moment in the process of interpretation when they appear. In this phase the task is to arrange regulations (separately or in the context of a number of regulations) according to their validity. In the first place the authors deal with notion and terminological distinctions and then they move on to analyse the process of interpreting a legal regulation, focusing mainly on two types of regulations, which are peripheral and central regulations. The further part of the article deals with changes to the regulation text. The problems of regulation derogation, i.e. when a regulation is abolished at a certain moment, are not by themselves - neither directly nor even indirectly - included among interpretive procedures, especially if they should refer to a peripheral regulation proper or a central one for which no modifying regulations have been made. Because of the exceptional role of modifying regulations abolishing any of them becomes particularly significant for the interpretive purposes as it results in changing the content of a norm, so far expressed in a given central regulation and also from a given modifying regulation before its abolition. The issue of derogation is connected with the broad understanding o f binding, which embraces the temporal, personal, and territorial aspect. In the discussion of this issue the authors concentrate on the first of these aspects. In the problem of regulation abolition they also emphasise the great significance of intertemporal regulations, which they consider to modify the range of abolition expressed in an abolishing regulation and which in this respect play an „anti-derogative” role. In the authors’ view, the problem of regulation derogation becomes an element of rational interpretation, being a phase standardizing the validity of peripheral or central regulations, as well as supplementary or modifying regulations at a certain moment (validating the binding of these regulations at a selected moment).
ARRANGING PHASE OF INTERPRETATION OF LAW